Active and Passive Smart Structures and Integrated Systems XVII 2023
DOI: 10.1117/12.2657942
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric-array-based MISO diagnostic system for CNN-condition monitoring of bearing/gearbox instruments

Abstract: The article presents a novel MISO (multi-input-single-output) diagnostic system suitable for spatial condition monitoring of bearing/gearbox instruments with multi-location defects. The sensor array consists of three piezoelectric patches: one is attached to the surface of the bearing house and the other two connected in parallel are mounted on the wall of the planetary gear. These two sets of patches are electrically connected in series for sensing the fault signals whose sources of anomalies come from either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…To optimize the frequency response, it can be shown that the inductance magnitude L is determined by the resonant condition L * = 1 w 2 Cp . 38 Next, for spatial condition monitoring in rotational machines, a sensor array model developed by Lo et al 38 is briefly described here. In the present setup shown in Fig.…”
Section: Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…To optimize the frequency response, it can be shown that the inductance magnitude L is determined by the resonant condition L * = 1 w 2 Cp . 38 Next, for spatial condition monitoring in rotational machines, a sensor array model developed by Lo et al 38 is briefly described here. In the present setup shown in Fig.…”
Section: Modelmentioning
confidence: 99%
“…To differentiate between the 12 health states detailed in Table 1, Lo et al developed a deep learning approach using CNN as outlined in their work. 38 CNN efficiently extracts local features from input data through convolutional layers with various filters, reducing the neural network size through pooling while preserving essential information. The CNN architecture, depicted in Fig.…”
Section: Cnn and Multi-task Cnnmentioning
confidence: 99%
See 2 more Smart Citations